2007
DOI: 10.1029/2007jd008472
|View full text |Cite
|
Sign up to set email alerts
|

Gridded data set of the stable isotopic composition of precipitation over the eastern and central Mediterranean

Abstract: [1] An attempt is made to produce 10 0 Â 10 0 gridded data sets of the isotopic composition of precipitation across the central and eastern Mediterranean. Following previous studies, statistical models are developed using all existing isotopic data from the area, aggregated on seasonal and annual bases. Various combinations of geographical and meteorological parameters are examined. Initial gridded isotopic data sets are obtained by applying these models to gridded geographical and meteorological data. The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 38 publications
(50 reference statements)
4
39
0
Order By: Relevance
“…These values represent approximately 6% and 9% of the total range of observed values, and are much smaller than the uncertainties typically associated with global water d 2 H models (Bowen and Revenaugh 2003). This result is consistent with other studies that have shown that region-specific models can provide enhanced water isotope prediction accuracy compared to global analyses (Hobson et al 2004, Dutton et al 2005, Lykoudis and Argiriou 2007, Lechler and Niemi 2011. Our prediction map depicts strong, dominantly meridional, …”
Section: Spatial Analysissupporting
confidence: 80%
“…These values represent approximately 6% and 9% of the total range of observed values, and are much smaller than the uncertainties typically associated with global water d 2 H models (Bowen and Revenaugh 2003). This result is consistent with other studies that have shown that region-specific models can provide enhanced water isotope prediction accuracy compared to global analyses (Hobson et al 2004, Dutton et al 2005, Lykoudis and Argiriou 2007, Lechler and Niemi 2011. Our prediction map depicts strong, dominantly meridional, …”
Section: Spatial Analysissupporting
confidence: 80%
“…The oxygen isotope composition of modern freshwater in the UK is relatively well known, with 18 O between -9.0‰ and -4.5‰, with the highest values (>~ -5.0‰) being isolated to the Outer Hebrides and the extreme west coast of Cornwall (Darling and Talbot, 2003;Darling et al, 2003 Lecolle et al, 1985;Longinelli and Selmo, 2003;Lykoudis and Argiriou, 2007). Luz et al 1984;Levinson et al 1987;).…”
Section: Establishing a Uk Oxygen Isotope Rangementioning
confidence: 99%
“…Statistical or geostatistical models of precipitation isoscapes have been proposed for the globe (Bowen and Wilkinson, 2002;Bowen and Revenaugh, 2003;Terzer et al, 2013), United States (Dutton et al, 2005), Austria (Liebminger et al, 2006a, b), Mediterranean (Lykoudis and Argiriou, 2007), Mongolia , China (Liu et al, 2008), Canada (Delavau et al, 2011), and Ireland (Fischer and Baldini, 2011). These isoscape models are useful in predicting isotope ratios at locations where no measured values are available or in integrating them over a spatial extent (e.g., river basin or smaller catchment).…”
Section: Introductionmentioning
confidence: 99%
“…In statistical models, although this uncertainty is usually evaluated by goodness-of-fit (to calibration data), few studies have validated the models using data independent of model development (Lykoudis and Argiriou, 2007). Geostatistical models do not allow for any estimates of prediction errors because they are optimized to completely fit modeled isotope ratios to observed ones (Bowen, 2010b).…”
Section: Introductionmentioning
confidence: 99%